Some Fallacies in the Interpretation of Social Cost - Knight, F. H. (Quarterly Journal of Economics, 1924)
Arguments for social interference developed by Pigou and Graham illustrate common misinterpretations of the meaning of cost and its variation with output, 582. — I. The private owner of a natural opportunity secures maximum return from it by charging that rent which halts the application of investment at the point which is socially most advantageous, 584. — II. The notion of decreasing cost is a fallacy; competitive price fixation under decreasing cost or increasing returns an impossible situation, 592. — III. The law of comparative advantage in international trade is fundamentally sound, 599. — Importation a method of using resources to produce the imported good, and will be employed under competitive conditions only when more efficient than a direct method, 603. — The competitive system has important defects, but they lie outside the mechanical theory of exchange relations, 605.